Student's Perception Of Online Learning In Bahasa Indonesia Courses During The Covid-19 Pandemic (Equilibrium: Jurnal Pendidikan, 2022)
Abstract. The purpose of this study was to determine student perceptions of online learning during the COVID-19 pandemic. The method used in this study is a quantitative approach using survey methods. Through this method, data is obtained based on the questionnaire documentation distributed through Google Forms. The subjects of this research are STIE Dwi Sakti Baturaja students who take Indonesian language courses, totaling 60 people. Subject selection using purposive sampling method. The results show that 50% of learning accesses easily, 25% of online learning provides high learning motivation, 51% of learning materials are complete and easily accessible, 35% of online learning helps me understand learning materials, 53% can do online learning independently during shopping. online, 60% of the ability to use technology increases during online learning, 50% of lecturers respond to questions and opinions that arise, 22% of interactions between lecturers and students are intimate, 32% of online learning makes students actively involved in asking questions and giving opinions during the process learning, 46% of online learning makes it easy to collaborate with fellow students (group work), 53% of online learning makes students believe their scores will increase, and 51% of online learning room facilities prepared by dictionaries are very helpful. As for this online learning barrier, namely the lack of motivation provided so that the learning atmosphere is not conducive. Not only that, the level of communication that exists between students and lecturers is considered poor because miscommunication often occurs.
Keywords: students perceptions; online learning; pandemi Covid-19